A whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material and preparation method thereof

By introducing sulfonic acid groups and whisker carbon nanotubes into the sulfonated polyether ether ketone material and using alkyl benzene sulfonate dispersants to enhance the bonding, the problem of poor bonding of carbon nanotubes and polyether ether ketone materials in the prior art is solved, and a low friction, wear resistance and high load-bearing water-lubricated bearing material is achieved.

CN119220081BActive Publication Date: 2025-02-28JIHUA LAB
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411730901.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The combination of the existing wear-resistant carbon nanotube polyether ether ketone composite materials and the polyether ether ketone materials is average, resulting in high friction coefficient, poor load-bearing capacity, and severe wear at low speeds.

Method used

By introducing hydrophilic sulfonic acid groups and branched whisker carbon nanotubes into the sulfonated polyether ether ketone material, and dispersing the whisker carbon nanotubes with alkyl benzene sulfonate dispersants, the bonding of the polyether ether ketone material and the whisker carbon nanotubes are enhanced and the surface strength and lubricating properties of the material are improved.

Benefits of technology

It effectively reduces the friction coefficient, improves the friction reduction and wear resistance of the material, enhances the load-bearing capacity, reduces wear at low speeds, and extends the service life of the bearing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220081B_ABST
    Figure CN119220081B_ABST
Patent Text Reader

Abstract

This invention discloses a sulfonated polyether ether ketone (PEEK) water-lubricated bearing material doped with whisker carbon nanotubes and its preparation method, belonging to the field of polymer materials technology. The method includes steps such as whisker carbon nanotube dispersion, doping with whisker carbon nanotubes, carbon fibers, and graphite, cold pressing, and sintering. By introducing hydrophilic sulfonic acid groups and branched whisker carbon nanotubes into the sulfonated PEEK material, the material effectively adsorbs hydrated cations from seawater, forming a hydrated lubricating layer on the material surface. Furthermore, the doped graphite, carbon fibers, and polymer interfaces within the material provide bridging and toughening. In addition, by dispersing the whisker carbon nanotubes using an alkylbenzene sulfonate dispersant, the sulfonic acid groups interact with the surface dispersant, enhancing the bonding between the PEEK material and the whisker carbon nanotubes and improving the surface strength of the material. This solves the problems of poor load-bearing capacity and severe wear at low speeds in existing PEEK composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a whisker carbon nanotube-doped sulfonated polyetheretherketone water-lubricated bearing material and a preparation method thereof. Background Art

[0002] Water-lubricated bearings, as a new and environmentally friendly device, have attracted widespread attention from researchers. Their uniqueness lies in their ability to work stably and reliably under water lubrication rather than grease lubrication conditions. They have the characteristics of simple structure, easy processing, pollution-free, and long service life. They can solve the problems of environmental pollution and resource waste caused by lubricating oil leakage in ship transmission systems from the source, and are conducive to building a new type of ship propulsion system that is pollution-free, widely available, and highly stable. Therefore, water-lubricated bearings have broad application prospects, especially in ship rudder bearings, stern bearings, centrifugal pumps, hydro-turbine generators, water circulation systems and other components.

[0003] When the ship propulsion system is started, the bearing speed is too low and is in a boundary lubrication state, making it difficult to form a complete lubricating water film on its surface. Moreover, under the action of the main shaft and seawater pressure, the bearing load-bearing part is easily deformed, the bearing clearance is reduced, the contact area between the bearing and the sleeve is increased, and the interface roughness peaks are in contact with each other and the interaction force is higher than the material yield stress, which will cause the roughness peaks to deform and break, and eventually cause serious wear of the bearing base material and generate a lot of friction noise, which seriously affects the operation of the ship and greatly shortens the service life of the bearing. Therefore, the preparation technology and evaluation system of high-performance, low-wear, and high-durability water-lubricated bearings urgently need to be established.

[0004] The idea of ​​fiber-reinforced polymer materials originates from the high orientation, high strength and high toughness of fibers, which can be used to improve the mechanical strength, chemical stability and thermal stability of polymer bearing materials. Researchers have confirmed that fiber reinforcement can effectively improve the friction reduction and wear resistance of polyetheretherketone-based composite materials, but the chopped fibers usually have poor bonding with the matrix, and are more likely to form cracks at the interface between the lubricating particles and the matrix during friction and wear, accelerating the failure and damage of the material. Therefore, researchers have further developed whisker-doped polyetheretherketone materials (polymer bearing materials). Whiskers have a branched dendrite-like structure, which can be embedded in polyetheretherketone materials to enhance the bonding between the lubricating particles and the matrix. For example, a Chinese patent document with publication number CN107141714A discloses a method for preparing a wear-resistant carbon nanotube polyetheretherketone composite material, which improves the wear-reducing and wear-resistant properties of the polyetheretherketone material by adding carbon nanotube powder to the polyetheretherketone. However, the bonding between the carbon nanotube powder and the polyetheretherketone material is general, and the friction coefficient of the disclosed wear-resistant carbon nanotube polyetheretherketone composite material is 0.19-0.28. The polyetheretherketone composite material still has the problem of high friction coefficient.

[0005] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention

[0006] The purpose of the present invention is to provide a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material and a preparation method, aiming to solve the problem that the existing wear-resistant carbon nanotube polyetheretherketone composite materials have general bonding properties between carbon nanotube powder and polyetheretherketone materials and still have a high friction coefficient.

[0007] To achieve the above object, the solution provided by the present invention is:

[0008] The present invention provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising the following steps:

[0009] S001. The carbon nanotube whiskers and an organic solvent are added to a flask, and then an alkylbenzene sulfonate dispersant is added to the flask, mechanically stirred at room temperature, and then the product is removed and bottled to obtain a carbon nanotube whisker dispersion;

[0010] S002. The sulfonated polyetheretherketone powder, carbon fiber and graphite are added to a beaker, and then the whisker carbon nanotube dispersion and an organic solvent are added to the beaker;

[0011] S002. The sulfonated polyetheretherketone powder, carbon fiber and graphite are added to a beaker, and then the whisker carbon nanotube dispersion and an organic solvent are added to the beaker;

[0012] S003. The sulfonated polyetheretherketone powder, carbon fiber, graphite and carbon nanotube whiskers were uniformly mixed using a high-speed homogenizer;

[0013] S004. The mixed material is filtered to remove the organic solvent in the material. After the organic solvent is removed, the mixed material is dried;

[0014] S005. Place the dried and evenly mixed material in a mold for cold pressing, and after cold pressing, place the material in a muffle furnace for sintering.

[0015] Optionally, in step S001, the alkylbenzene sulfonate dispersant includes at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, and sodium hexadecylbenzene sulfonate.

[0016] Optionally, in step S002, the method for preparing sulfonated polyetheretherketone powder comprises the following steps:

[0017] H001. Dry the polyetheretherketone powder in a drying oven;

[0018] H002. Add an organic solvent into a flask, then add the dried polyetheretherketone powder into the flask, then drop a sulfonating agent into the flask, and mechanically stir to allow the polyetheretherketone to react with the sulfonating agent to generate sulfonated polyetheretherketone, wherein the sulfonating agent includes at least one of chlorosulfonic acid and aminosulfonic acid.

[0019] Optionally, in step S001, the organic solvent includes ethanol and acetone, and the mass ratio of ethanol to acetone is (0.8-1.2):1.

[0020] Optionally, in step S001, the mass ratio of the organic solvent to the whisker carbon nanotubes is 100:(0.1-5).

[0021] Optionally, in step S001, the mass ratio of the organic solvent to the alkylbenzene sulfonate dispersant is 100:(0.05-1).

[0022] Optionally, in step S002, the mass ratio of carbon fiber to graphite is (0.8-1.2):1.

[0023] Optionally, in step S002, the ratio of the total mass of carbon fiber and graphite to the mass of sulfonated polyetheretherketone is (35-40):(60-65).

[0024] Optionally, in step S003, the mass ratio of the whisker carbon nanotubes to the sulfonated polyetheretherketone powder is (0.1-7):100.

[0025] The invention also provides a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, which is prepared by the preparation method of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material.

[0026] The beneficial effects of the present invention are: a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material and a preparation method thereof, by introducing hydrophilic sulfonic acid groups and whisker carbon nanotubes with a branched structure into the sulfonated polyetheretherketone material, the sulfonated polyetheretherketone material can effectively adsorb hydrated cations in seawater, form a hydrated lubricating layer on the surface of the material, and bridge and toughen the interface between the graphite, carbon fiber and polymer doped inside the material. In addition, the present invention disperses the whisker carbon nanotubes by means of an alkylbenzene sulfonate dispersant, so that the sulfonic acid groups interact with the surface dispersant of the whisker carbon nanotubes, so that the binding of the polyetheretherketone material and the whisker carbon nanotubes is enhanced, the surface strength of the polyetheretherketone material can be improved, and in practical applications, it can effectively play a role in reducing friction and resisting wear, thereby solving the problems of poor bearing capacity and severe wear at low speed of the existing polyetheretherketone composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1The present invention provides a flow chart of a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material.

[0028] Figure 2 This is the morphology of the wear scar of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material after testing. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present invention provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising the following steps:

[0031] S001. The whisker carbon nanotubes and an organic solvent were added to a three-necked flask, and then an alkylbenzene sulfonate dispersant was added to the three-necked flask, mechanically stirred at room temperature for 3h, and then the product was removed and bottled to obtain a whisker carbon nanotube dispersion;

[0032] S002. The sulfonated polyetheretherketone powder, carbon fiber and graphite are added to a beaker, and then the whisker carbon nanotube dispersion and the organic solvent are added to the beaker in sequence;

[0033] S003. The sulfonated polyetheretherketone powder, carbon fiber, graphite and carbon nanotube whiskers were uniformly mixed using a high-speed homogenizer;

[0034] S004. The mixed material is filtered to remove the organic solvent in the material. After the organic solvent is removed, the mixed material is dried;

[0035] S005. Place the dried and evenly mixed material in a mold for cold pressing, and after cold pressing, place the material in a muffle furnace for sintering.

[0036] In step S001 of the preparation method, the whisker carbon nanotubes can be obtained through commercial channels, and the organic solvent is combined with an alkylbenzene sulfonate dispersant to disperse the whisker carbon nanotubes in the organic solvent; when the alkylbenzene sulfonate dispersant disperses the whisker carbon nanotubes, the hydrophobic groups interact with the whisker carbon nanotubes, which helps the whisker carbon nanotubes to disperse in the organic solvent. Taking out the product, bottling and sealing it can reduce the volatilization of the organic solvent and prevent the whisker carbon nanotubes from agglomerating in the organic solvent.

[0037] When the whisker carbon nanotubes are severely agglomerated in the organic solvent, it is difficult to grasp the content of the whisker carbon nanotubes in the whisker carbon nanotube dispersion in step S002, and it is impossible to ensure that the water lubrication and mechanical properties of the prepared whisker carbon nanotube-doped sulfonated polyetheretherketone water-lubricated bearing material meet the use requirements of the bearing base.

[0038] In step S002 of the above preparation method, the sulfonated polyetheretherketone dispersant is obtained by sulfonation modification of the polyetheretherketone material. Compared with the polyetheretherketone material that has not been sulfonated, the sulfonated polyetheretherketone material introduces hydrophilic sulfonic acid groups. Therefore, the sulfonated polyetheretherketone material is not only more hydrophilic, but also easier to combine with the whisker carbon nanotubes with alkylbenzene sulfonate dispersants adsorbed on the surface, so that the polyetheretherketone material can be more tightly combined with the whisker carbon nanotubes, and the whisker carbon nanotubes are difficult to peel off from the polyetheretherketone material, thereby effectively improving the friction reduction and anti-wear ability of the polyetheretherketone composite material.

[0039] In step S002 of the above preparation method, the carbon fiber has very high strength and modulus. By doping the carbon fiber into the sulfonated polyetheretherketone powder, the mechanical properties (compression strength and surface hardness) of the water-lubricated bearing material can be significantly improved, so that the material has better resistance under low-speed and heavy-load conditions. When graphite is doped into the sulfonated polyetheretherketone powder, a lubricating film can be quickly formed on the friction surface when the material rubs, thereby preventing direct contact between the friction surfaces, so that the friction coefficient of the water-lubricated bearing material can be reduced.

[0040] Optionally, in step S002, the mass ratio of carbon fiber to graphite is (0.8-1.2): 1. When the mass ratio of carbon fiber to graphite is within this range, the mechanical properties of the prepared water-lubricated bearing material will not be weakened, and the friction properties of the material can also be enhanced.

[0041] In step S003 of the above preparation method, the rotation speed of the high-speed homogenizer is 20 krpm and the mixing time is 30 s, thereby making the materials evenly mixed and the obtained water-lubricated bearing material have uniform performance.

[0042] In step S004 of the above preparation method, the organic solvent may be ethanol, so that even if ethanol remains on the surface of the material, the ethanol can be volatilized from the surface of the material. In addition, the drying temperature may be 80°C, and under the premise of ensuring that the ethanol is volatilized, the safety hazard will not increase.

[0043] In step S005 of the preparation method, the pressure of cold pressing is 10-120 MPa, and the temperature of cold pressing is 20-30° C. By controlling the pressure and temperature of cold pressing within the above parameter range, the sulfonated polyetheretherketone powder, whisker carbon nanotubes, graphite and carbon fiber can be more closely combined, and the strength and lubrication performance of the surface of the water-lubricated bearing material can be enhanced.

[0044] In step S005 of the above preparation method, the sintering temperature is 360-380°C and the sintering time is 4-5h. When the sintering temperature and sintering time are controlled within the above parameter range, the sulfonated polyetheretherketone powder can be fully melted, and the sulfonated polyetheretherketone powder, whisker carbon nanotubes, graphite and carbon fiber are more closely combined, so that the mechanical properties and lubrication properties of the water-lubricated bearing material are enhanced. If the sintering temperature is too high, the sulfonated polyetheretherketone powder will turn black and decompose, so that the mechanical properties and lubrication properties of the water-lubricated bearing material will be weakened.

[0045] It can be seen that, since the hydrophilic sulfonic acid groups and the whisker carbon nanotubes with branched structures are introduced into the sulfonated polyetheretherketone material of the present invention, the sulfonated polyetheretherketone material can effectively absorb the hydrated cations in the seawater and form a hydrated lubricating layer on the surface of the material, and the whisker carbon nanotubes can bridge and toughen the interface between the graphite, carbon fiber and polymer doped inside the material. In addition, the present invention disperses the whisker carbon nanotubes by means of alkylbenzene sulfonate dispersants, so that the sulfonic acid groups can interact with the surface dispersants of the whisker carbon nanotubes, so that the binding of the polyetheretherketone material and the whisker carbon nanotubes is enhanced, and the surface strength of the polyetheretherketone material can be improved, which can effectively reduce friction and resist wear in practical applications, thereby solving the problems of poor load-bearing capacity and severe wear at low speed of the existing polyetheretherketone composite materials.

[0046] Optionally, in step S001, the alkylbenzene sulfonate dispersant includes at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, and sodium hexadecylbenzene sulfonate. The above dispersants are all alkylbenzene sulfonate dispersants, and the hydrophilic groups on them can make the whisker carbon nanotubes interact with the sulfonic acid groups on the sulfonated polyetheretherketone material, so that the polyetheretherketone material can enhance the binding property with the whisker carbon nanotubes.

[0047] Optionally, in step S001, the organic solvent includes ethanol and acetone, and the mass ratio of ethanol to acetone is (0.8-1.2): 1. The present invention finds that when the amount of ethanol is too much, the whisker carbon nanotubes are easy to settle in the organic solvent, and the dispersion liquid will be stratified; and when the amount of acetone is too much, the acetone is easy to volatilize, which increases the concentration of the whisker carbon nanotubes in the dispersion liquid, and the whisker carbon nanotubes have the problem of agglomeration. Therefore, the present invention controls the mass ratio of ethanol to acetone within the above range, which can ensure that the whisker carbon nanotubes are effectively dispersed and the concentration of the whisker carbon nanotubes in the dispersion liquid is controllable.

[0048] Optionally, in step S001, the mass ratio of the organic solvent to the whisker carbon nanotubes is 100:(0.1-5). If the amount of whisker carbon nanotubes added to the organic solvent is too much, the whisker carbon nanotubes are prone to agglomeration.

[0049] Optionally, in step S001, the mass ratio of the organic solvent to the alkylbenzene sulfonate dispersant is 100:(0.05-1). If the amount of dispersant is too much, the whisker carbon nanotubes are easy to agglomerate, and if the amount of dispersant is too little, the dispersion effect is not obvious.

[0050] Optionally, in step S002, the ratio of the total mass of carbon fiber and graphite to the mass of sulfonated polyetheretherketone is (35-40): (60-65). Excessive doping of carbon fiber and graphite will weaken the compressive strength and tribological properties of the water-lubricated bearing material. Therefore, the present invention controls the ratio of the total mass of carbon fiber and graphite to the mass of sulfonated polyetheretherketone within the above range, so that the mechanical properties and mechanical properties of the water-lubricated bearing material can be enhanced.

[0051] Although excessive doping of whisker carbon nanotubes can improve the mechanical properties of sulfonated polyetheretherketone materials, the friction performance of sulfonated polyetheretherketone materials is not significantly improved. Therefore, optionally, in step S003, the mass ratio of whisker carbon nanotubes to sulfonated polyetheretherketone powder is (0.1-7):100.

[0052] Optionally, in step S002, the method for preparing sulfonated polyetheretherketone powder comprises the following steps:

[0053] H001. Dry the polyetheretherketone powder in a drying oven;

[0054] H002. Add the organic solvent into a three-necked flask, then add the dried polyetheretherketone powder into the three-necked flask, then drop the sulfonating agent into the three-necked flask, stir mechanically, and react at room temperature for 2.5 to 3.5 hours to make the polyetheretherketone react with the sulfonating agent to generate sulfonated polyetheretherketone.

[0055] In the above step H001, the drying temperature is 120° C. and the drying time is 8 hours to remove moisture from the polyetheretherketone powder, thereby avoiding serious agglomeration of polyetheretherketone particles and the reaction between water vapor and solvent, which is unfavorable to the sulfonation modification of polyetheretherketone.

[0056] In the above step H002, the mass ratio of the organic solvent to the polyetheretherketone powder is 100: (1-20), the mass ratio of the organic solvent to the sulfonating agent is 100: (1-10), and the organic solvent is composed of dichloromethane and tetrahydrofuran, and the volume ratio of dichloromethane and tetrahydrofuran is (10-90): (10-90). Dichloromethane and tetrahydrofuran are organic solvents, which can disperse the polyetheretherketone particles and avoid serious agglomeration of the polyetheretherketone particles, thereby facilitating the regulation of the sulfonation degree of the polyetheretherketone, so that the sulfonated polyetheretherketone material has higher surface hardness and better friction performance; in addition, dichloromethane and tetrahydrofuran are safer and easier to scale up the test than other organic solvents, so that they can be used for batch modification of polyetheretherketone powder, providing a guarantee for the application of polyetheretherketone materials to large components such as water-lubricated bearings.

[0057] The sulfonating agent includes at least one of chlorosulfonic acid and aminosulfonic acid. Compared with other types of sulfonating agents, the sulfonation reaction of chlorosulfonic acid, aminosulfonic acid and polyetheretherketone is controllable. When polyetheretherketone reacts with the sulfonating agent, no obvious agglomeration phenomenon will occur in the organic solvent, and no large amount of heat will be released, which is highly safe, thereby helping to control the sulfonation degree of polyetheretherketone materials, so that the sulfonated modified materials can have both high surface hardness and good friction performance, providing a guarantee for the application of polyetheretherketone materials in large components such as water-lubricated bearings (such as bushings).

[0058] In addition, the preparation method of sulfonated polyetheretherketone powder also includes the following steps:

[0059] H003. The reaction product of step H002 is poured into a container filled with ice water, and then the pH of the reaction product is adjusted to neutral with a pH adjuster;

[0060] H004. Wash and filter the reaction product with a neutral pH value with deionized water to obtain sulfonated polyetheretherketone powder.

[0061] In the above step H003, the reaction product is poured into a container filled with ice water to prevent the pH adjuster from releasing heat violently when adjusting the pH of the reaction product. The pH adjuster may be sodium hydroxide.

[0062] The present invention also provides a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, which is prepared by the preparation method of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material. The provided whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material can effectively adsorb hydrated cations in seawater, form a hydrated lubricating layer on the surface of the material, and bridge and toughen the interface between the graphite, carbon fiber and polymer doped inside the material. The surface dispersant of the whisker carbon nanotube interacts with the sulfonated polyetheretherketone matrix, so that the bonding between the polyetheretherketone material and the whisker carbon nanotube is enhanced, and the surface strength of the polyetheretherketone material can be improved. In practical applications, it can effectively reduce friction and resist wear, thereby solving the problems of poor load-bearing capacity and severe wear at low speed of existing polyetheretherketone composite materials.

[0063] In order to further illustrate the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material and the preparation method thereof provided by the present invention, the following examples and comparative examples are provided. Example 1

[0064] This embodiment provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising the following steps:

[0065] S001. 5 g of carbon nanotube whiskers and 500 g of an organic solvent were added to a three-necked flask, and then 1 g of sodium dodecyl sulfate was added. After mechanical stirring at room temperature for 3 h, the mixture was taken out and bottled to obtain a carbon nanotube whisker dispersion, wherein the organic solvent consisted of ethanol and acetone, and the mass ratio of ethanol to acetone was 1:1;

[0066] S002. 3 g of sulfonated polyetheretherketone powder, 0.5 g of carbon fiber and 0.5 g of graphite were added into a beaker, and then 0.4 g of a whisker carbon nanotube dispersion (the mass concentration of the whisker carbon nanotubes in the whisker carbon nanotube dispersion was 1%, the same below) and 50 g of ethanol were added into the beaker in sequence, and the concentration of the whisker carbon nanotubes in the whisker carbon nanotube dispersion was 1%;

[0067] S003. The sulfonated polyetheretherketone powder, carbon fiber, graphite and carbon nanotube whiskers were uniformly mixed using a high-speed homogenizer;

[0068] S004. The mixed material is filtered to remove ethanol and acetone in the material. After the ethanol and acetone are removed, the mixed material is dried at a drying temperature of 80°C;

[0069] S005. Place the dried and evenly mixed material in a mold for cold pressing, and place the material in a muffle furnace for sintering after cold pressing. The cold pressing pressure is 100 MPa, the cold pressing temperature is 25°C, the sintering temperature is 370°C, and the sintering time is 4 hours.

[0070] In this embodiment, in step S001, the mass ratio of the organic solvent to the whisker carbon nanotubes is 100:1, and the mass ratio of the organic solvent to the dispersant is 100:0.2; in step S002, the mass ratio of carbon fiber to graphite is 1:1, the ratio of the total mass of carbon fiber and graphite to the mass of sulfonated polyetheretherketone is 33:100, the mass ratio of whisker carbon nanotubes to sulfonated polyetheretherketone powder is 0.13:100, and the mass ratio of ethanol to sulfonated polyetheretherketone powder is 100:6. Example 2

[0071] This embodiment provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising step S001, step S002, step S003, step S004 and step S005. Among them, step S003, step S004 and step S005 are the same as in Example 1, in step S001, the alkylbenzene sulfonate dispersant is sodium hexadecylbenzene sulfonate, and the rest is the same as in Example 1, in step S002, the mass of the whisker carbon nanotube dispersion is 0.8g, and the rest is the same as in Example 1. In this embodiment, the mass ratio of whisker carbon nanotubes to sulfonated polyetheretherketone powder is 0.26:100. Example 3

[0072] This embodiment provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising step S001, step S002, step S003, step S004 and step S005. Among them, step S003, step S004 and step S005 are the same as in Example 1, in step S001, the alkylbenzene sulfonate dispersant is sodium dodecylbenzene sulfonate, and the rest is the same as in Example 1, in step S002, the mass of the whisker carbon nanotube dispersion is 2g, and the rest is the same as in Example 1. In this embodiment, the mass ratio of whisker carbon nanotubes to sulfonated polyetheretherketone powder is 0.67:100. Example 4

[0073] This embodiment provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising steps S001, S002, S003, S004 and S005. Among them, steps S001, S003, S004 and S005 are the same as those in Example 1, in step S002, the mass of the whisker carbon nanotube dispersion is 4g, and the rest is the same as in Example 1. In this embodiment, the mass ratio of the whisker carbon nanotube to the sulfonated polyetheretherketone powder is 1.3:100. Example 5

[0074] This embodiment provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising step S001, step S002, step S003, step S004 and step S005. Among them, step S001, step S003, step S004 and step S005 are the same as in Example 1, in step S002, the mass of the whisker carbon nanotube dispersion is 12g, and the rest is the same as in Example 1. In this embodiment, the mass ratio of the whisker carbon nanotube to the sulfonated polyetheretherketone powder is 4:100. Example 6

[0075] This embodiment provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising step S001, step S002, step S003, step S004 and step S005. Among them, step S001, step S003, step S004 and step S005 are the same as in Example 1, in step S002, the mass of the whisker carbon nanotube dispersion is 20g, and the rest is the same as in Example 1. In this embodiment, the mass ratio of the whisker carbon nanotube to the sulfonated polyetheretherketone powder is 6.7:100.

[0076] Comparative Example 1

[0077] This comparative example provides a method for preparing a particle-doped sulfonated polyetheretherketone water-lubricated bearing material, comprising the following steps:

[0078] D001. 3 g of sulfonated polyetheretherketone powder, 0.5 g of carbon fiber and 0.5 g of graphite were added to a beaker, and then 50 g of ethanol was added to the beaker;

[0079] D002. Using a high-speed homogenizer, sulfonated polyetheretherketone powder, carbon fiber and graphite are uniformly mixed;

[0080] D003. Filter the uniformly mixed material to remove ethanol from the material. After the ethanol is removed, dry the uniformly mixed material at a drying temperature of 80°C;

[0081] D004. Place the dried and evenly mixed material in a mold for cold pressing, and then place the material in a muffle furnace for sintering. The cold pressing pressure is 100 MPa, the cold pressing temperature is 25°C, the sintering temperature is 370°C, and the sintering time is 4 hours.

[0082] Comparative Example 2

[0083] This comparative example provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising step D001, step D002, step D003, step D004 and step D005. Among them, step D001, step D003, step D004 and step D005 are the same as in Example 4, in step S002, carbon fiber and graphite are not added, and the rest are the same as in Example 4.

[0084] Comparative Example 3

[0085] This comparative example provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising step D001, step D002, step D003, step D004 and step D005. Among them, step D002, step D003, step D004 and step D005 are the same as in Example 4, in step D001, the dispersant is sodium dodecyl sulfate, and the rest is the same as in Example 4.

[0086] Comparative Example 4

[0087] This comparative example provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising step D001, step D002, step D003, step D004 and step D005. Among them, step D001, step D003, step D004 and step D005 are the same as in Example 4, in step D002, the mass of carbon fiber is 0.83g, the mass of graphite is 0.17g (the mass ratio of carbon fiber to graphite is 5:1), and the rest is the same as in Example 4.

[0088] Comparative Example 5

[0089] This comparative example provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising step D001, step D002, step D003, step D004 and step D005. Among them, step D001, step D003, step D004 and step D005 are the same as in Example 4, in step D002, the mass of carbon fiber is 0.17g, the mass of graphite is 0.83g, and the rest is the same as in Example 4.

[0090] Comparative Example 6

[0091] This comparative example provides a method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, comprising step D001, step D002, step D003, step D004 and step D005. Among them, step D001, step D003, step D004 and step D005 are the same as in Example 4, in step D002, the mass of carbon fiber is 1g, the mass of graphite is 1g, and the rest is the same as in Example 4.

[0092] The friction performance of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing materials prepared in Examples 1 to 6, the particle doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 1, and the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing materials prepared in Comparative Example 2 to 6 were tested using a UMT rotary friction and wear testing machine. The test conditions were: rotation speed 200 rpm, load 15 N, rotation radius 5 mm, and 3% sodium chloride solution was selected as the test environment. The test results are shown in Table 1.

[0093] The surface hardness of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing materials prepared in Examples 1 to 6, the particle doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 1, and the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing materials prepared in Comparative Examples 2 to 6 were tested using a Shore hardness tester. Samples with a diameter of 20 mm and a height of 5 mm were selected for the test. The test results are shown in Table 2.

[0094] Table 1

[0095] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 0.023 0.020 0.013 0.0096 0.016 0.021 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 0.025 0.043 0.013 0.026 0.036 0.050

[0096] Table 2

[0097] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 85 86 86.5 88 89 88 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 83 81 87 88.5 84 80

[0098] It can be seen from the test results in Table 1 that the friction coefficients of the whisker carbon nanotube-doped sulfonated polyetheretherketone water-lubricated bearing materials prepared in Examples 1 to 6 are all less than the particle-doped sulfonated polyetheretherketone water-lubricated bearing materials prepared in Comparative Example 1, and when the mass ratio of whisker carbon nanotubes to sulfonated polyetheretherketone powder is 1.3:100, the friction coefficient of the material can be reduced to 0.0096, reaching a super-slip state. This is because after the whisker carbon nanotubes are doped in the sulfonated polyetheretherketone material, the branched structure of the whisker carbon nanotubes bridges and toughens the interface, and the sulfonate groups on the surface of the whisker carbon nanotubes interact with the sulfonated polyetheretherketone, further enhancing the binding of the material interface with the doped whisker carbon nanotubes, sharing the contact stress between the water-lubricated bearing material and the dual surface, reducing the debonding and peeling of the doped material, and effectively reducing the friction and wear of the dual surface. In addition, after the whisker carbon nanotubes are doped in the sulfonated polyetheretherketone material, the mechanical properties of the material can also be significantly improved.

[0099] The friction coefficient of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 2 is significantly higher than the friction coefficient of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Examples 1 to 6. This is because the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 2 is not doped with carbon fiber and graphite, resulting in that the mechanical properties and friction properties of the water-lubricated bearing material are not enhanced. It can also be seen from the hardness test results in Table 2 that the surface hardness of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 2 is significantly lower than the surface hardness of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Examples 1 to 6.

[0100] The friction coefficient of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 3 is higher than that of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Example 4, and the surface hardness of the material prepared in Comparative Example 3 is also not as good as the surface hardness of the material prepared in Example 4. This is because the dispersant used in Comparative Example 3 is an alkyl sulfate dispersant, and the ability of such dispersants to enhance the bonding between whisker carbon nanotubes and sulfonated polyetheretherketone materials is not as good as that of alkyl sulfonate dispersants.

[0101] Although the surface hardness of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 4 is higher than that of the material prepared in Example 4, its friction coefficient is significantly higher than that of the material prepared in Example 4. This is because the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 4 contains excessive carbon fiber doping.

[0102] The mechanical properties (surface hardness) and friction properties (friction coefficient) of the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 5 are significantly inferior to those of the material prepared in Example 4. This is because the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 5 contains excessive graphite doping, which makes the graphite unable to play a role in reducing the friction coefficient of the water-lubricated bearing material.

[0103] The mechanical properties (surface hardness) and friction properties (friction coefficient) of the whisker carbon nanotube-doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 6 are not as good as those of the material prepared in Example 4. This is because the doping amount of carbon fiber and graphite is too high. Although it can improve the compressive strength and surface hardness of the water-lubricated bearing material and the tribological properties of the material, when the amount of sulfonated polyetheretherketone as the main phase is too small, the mechanical properties and friction properties of the water-lubricated bearing material are deteriorated.

[0104] The morphology of the wear scar of the whisker carbon nanotube-doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Example 1 and the particle-doped sulfonated polyetheretherketone water-lubricated bearing material prepared in Comparative Example 1 after the friction performance test was completed was observed using a three-dimensional white light interferometer. Figure 2 .from Figure 2 It can be seen that with the introduction of whisker carbon nanotubes into sulfonated polyetheretherketone, the wear depth of the polyetheretherketone material is reduced, and the furrows inside the wear mark are reduced, and the friction reduction and wear resistance of the material are improved. This shows that the introduction of whisker carbon nanotubes can effectively improve the tribological properties of polyetheretherketone composites.

[0105] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, characterized in that: The following steps are involved: S001. The carbon nanotube whiskers and an organic solvent are added to a flask, and then an alkylbenzene sulfonate dispersant is added to the flask, mechanically stirred at room temperature, and then the product is removed and bottled to obtain a carbon nanotube whisker dispersion; S002. The sulfonated polyetheretherketone powder, carbon fiber and graphite are added to a beaker, and then the whisker carbon nanotube dispersion and an organic solvent are added to the beaker; S003. The sulfonated polyetheretherketone powder, carbon fiber, graphite and carbon nanotube whiskers were uniformly mixed using a high-speed homogenizer; S004. The mixed material is filtered to remove the organic solvent in the material. After the organic solvent is removed, the mixed material is dried; S005. The dried and evenly mixed material is placed in a mold for cold pressing, and after cold pressing, the material is placed in a muffle furnace for sintering; In step S001, the alkylbenzene sulfonate dispersant includes at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, and sodium hexadecylbenzene sulfonate; In step S002, the mass ratio of carbon fiber to graphite is (0.8-1.2): 1; In step S002, the ratio of the total mass of the carbon fiber and the graphite to the mass of the sulfonated polyetheretherketone is 1:

3.

2. The method for preparing the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material according to claim 1, characterized in that: In step S002, the method for preparing sulfonated polyetheretherketone powder comprises the following steps: H001. Dry the polyetheretherketone powder in a drying oven; H002. Add an organic solvent into a flask, then add the dried polyetheretherketone powder into the flask, then drop a sulfonating agent into the flask, and mechanically stir to allow the polyetheretherketone to react with the sulfonating agent to generate sulfonated polyetheretherketone, wherein the sulfonating agent includes at least one of chlorosulfonic acid and aminosulfonic acid.

3. The method for preparing the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material according to claim 1, characterized in that: In step S001, the organic solvent includes ethanol and acetone, and the mass ratio of ethanol to acetone is (0.8-1.2):

1.

4. The method for preparing the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material according to claim 1, characterized in that: In step S001, the mass ratio of the organic solvent to the whisker carbon nanotubes is 100:(0.1-5).

5. The method for preparing the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material according to claim 1, characterized in that: In step S001, the mass ratio of the organic solvent to the alkylbenzene sulfonate dispersant is 100:(0.05-1). 6 . The method for preparing a whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material according to claim 1 , wherein in step S003 , the mass ratio of the whisker carbon nanotube to the sulfonated polyetheretherketone powder is (0.1-7):

100.

7. A whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material, characterized in that: The material is prepared by the method for preparing the whisker carbon nanotube doped sulfonated polyetheretherketone water-lubricated bearing material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of wear-resistant carbon nanotube polyether ether ketone composite material

    CN107141714A

  • High-toughness composite plastic and preparation method thereof

    CN116200041A

  • Porous sulfonated polyetheretherketone water-lubricated bearing material and preparation method thereof

    CN117327238A